2018
DOI: 10.25273/cheesa.v1i2.3035
|View full text |Cite
|
Sign up to set email alerts
|

Biobriket Limbah Kulit Durian dengan Pencelupan pada Minyak Jelantah

Abstract: <p class="E-JOURNALAbstractBody">Kulit Durian memiliki potensi sebagai sumber energi terbarukan. Isu tersebut menjadi <em>trending topic </em>bidang energi sebagai solusi kelangkaan minyak bumi dan gas. Kandungan selulosa kulit durian mencapai 64,51% menjadi sumber energi biobriket. Kulit durian menjadi salah satu opsi karena komposisi kulitnya mencapai 60-75%. Kulit durian ini mampu memperbesar densitas dan nilai ekonomis produk yang dihasilkan. Lalu, selain menggunakan kulit durian, penelit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
1
0
2
Order By: Relevance
“…The high ash content in durian skin charcoal biobriquettes is contrary to several similar studies, but is in line with the results obtained in research conducted by Nuriana et al who reported that the ash content of durian skin charcoal biobriquettes had an ash content of 18.18 % [19]. Apart from that, Efelina et al also reported that the ash content of durian peel biobriquettes with tapioca adhesive was 12.32% [20]. Ash is a residue from combustion that does not evaporate after burning at high temperatures.…”
Section: Ash Contentsupporting
confidence: 83%
“…The high ash content in durian skin charcoal biobriquettes is contrary to several similar studies, but is in line with the results obtained in research conducted by Nuriana et al who reported that the ash content of durian skin charcoal biobriquettes had an ash content of 18.18 % [19]. Apart from that, Efelina et al also reported that the ash content of durian peel biobriquettes with tapioca adhesive was 12.32% [20]. Ash is a residue from combustion that does not evaporate after burning at high temperatures.…”
Section: Ash Contentsupporting
confidence: 83%
“…Hal ini menunjukkan bahwa pencampuran perekat getah karet sebanyak 9 % pada penelitian ini menghasilkan kadar air yang cukup rendah dibandingkan dengan penelitian sebelumnya. Penelitian Efelina et al (2018) kadar air tanpa pencelupan dan setelah perlakuan dengan mencelupkan ke dalam minyak jelantah dari 11,93% menjadi 9,37%, kemudian penelitian Widodo, (2016) diperoleh kadar air dari 7,47% menjadi 6,86%. Hal ini membuktikan bahwa pada penelitian ini pencelupan briket dalam minyak jelantah mampu menghasilkan kadar air yang rendah dibandingkan penelitian terdahulu.…”
Section: Kadar Airunclassified
“…Dibandingkan dengan penelitian Saukani et al ( 2019) didapatkan nilai kalor 6.837-7.209 kal/g. Penelitian Efelina et al (2018) nilai kalor tanpa pencelupan dan setelah mencelupkan ke dalam minyak jelantah dari 5.076 kal/g menjadi 5.655 kal/g, kemudian penelitian Widodo, (2016) dari 6.741 kal/g menjadi 7.148 kal/g. Pada penelitian ini briket dengan menggunakan cangkang biji karet dan perekat getah karet menghasilkan nilai kalor yang tinggi (8.042 kal/g).…”
Section: Nilai Kalorunclassified
“…From the data above, the potential availability of durian peel is 124,494.22 tons/year [1]. Durian peel has a cellulose content that reaches 64.51% [2]. The high cellulose value in durian peel has the potential to be a source of energy to be used as biobriquettes.…”
Section: Research Backgroundmentioning
confidence: 99%